Snyder’s Vision Of The World As An Interbirth (Journal of Namibian Studies : History Politics Culture, 2023)
A lifelong Zen layman, Gary S. Snyder is the Pulitzer Awardee of 1975 and renowned as a deep ecologist, radical cultural visionary, and planetary poet. He has the deepest faith in the material universe as feminine. To some, he is a neo-tribal, reactionary, regressive mind. His poetry appears to be a network of philosophies like pataphysics, process philosophy, Eastern metaphysics, and some see him as a relativist, and others as an eclecticist. But Snyder’s poetic vision works especially within the Buddhist metaphysics of which a possible misreading is quite common, but it evidences an enabling capacity to rejuvenate the worldwide beliefs in the mother principle. Moreover, his poetry has been an intricately blended trope for ellipse, nature, consciousness, and philosophies, especially Zen. This paper proposes to take an Eastern view and reexamine how the poet explores the intricacies of life and meanings of human existence in the world as an interbirth. With Snyder, it is fascinating to see this world not as a holistic standard, but as a living throb of interdependent sentience.